Communication Effectiveness of Doctors and Patients, Loyalty, Word of Mouth, On Repurchase Intentions at District Public Hospital Tangerang, Indonesia - Rini Handayani; Endang Ruswanti; Mohamad Reza Hilmy; MF. Arrozi Adhikara (Penerbit Kemala Indonesia, 2021)
The dynamic state of society and the economy is sufficient, and the ease of access to information also influences patients’ choice of health care providers. The delivery of information between patients has a strong influence on the determination of the choice of service facilities that provide health services, due to service satisfaction and loyalty felt by the patients themselves, which will lead to the desire or intention to choose and reuse services in the hospital. The purpose of this study is to examine the impact of effective communication, patient loyalty, Word of Mouth on the intention to return to the Tangerang District General Hospital. A total of 105 patients were included in this quantitative study. Structural Equation Modelling analysis tool with Path Analysis statistical test was used in this study. The results showed that the effective communication between doctor and patient has a significant positive effect on patient loyalty. The influence of Word of mouth has direct impact on the intention to visit the hospital. Without word of mouth, effective communication and patient loyalty towards the wish to return to the hospital are possible.